History on trial my day in court with a Holocaust Denier - Lipstadt, Deborah E. 1947- (Ecco, 2005)
A chronicle of the author's five-year legal battle with writer David Irving, a prolific supporter of Holocaust denial, describes how the author and a team of experts defended against Irving's libel suit while exposing his distortions of history.
Includes index.
Keywords: Irving, David John Cawdell -- 1938- -- Trials, litigation, etc; Lipstadt, Deborah E -- Trials, litigation, etc; Lipstadt, Deborah E. -- 1947-; Irving, David John Cawdell -- 1938-; Penguin (Firm) -- Trials, litigation, etc; Geschichte 2000; Holocaust; Nationaal-socialisme; Ontkenning (algemeen); Revisionisme (geschiedenis); Judenvernichtung; Nationalsozialismus; Trials (Libel) -- England -- London; Holocaust, Jewish (1939-1945) -- Historiography; Prozess; Auschwitz-Lüge; Autobiografie -- 1998-2001